PENDEKATAN INOVATIF DALAM MEREKUNTRUKSI SISTEM PENDIDIKAN ISLAM MELALUI KOLABORASI ISO, TQM, DAN MBS - Muhammad Zaenul Lael; Subiyantoro; Erik Junaidi (Program Studi Manajemen Pendidikan Islam, 2025)
This research aims to explore innovative strategies in reconstructing the Islamic education system through the collaboration of ISO, Total Quality Management (TQM), and School-Based Management (SBM) approaches. The research method uses a descriptive qualitative approach based on literature study. Data collection techniques were carried out by collecting information from scientific papers such as books, journal articles, the internet, and other writings related to the literature review. The results show that ISO integration provides a framework for quality management based on international standards, TQM improves quality through the participation of all parties, and MBS strengthens school autonomy to meet local needs. These three collaborative approaches can create an education system that is holistic, sustainable and relevant to the needs of the times. In conclusion, the integration of ISO, TQM, and MBS contributes significantly to improving the quality of Islamic education, creating an optimal learning environment, and shaping a generation that is intellectually superior and morally good